Molecular Characterization Reveals Genetic Differences Between Wild and Captive Populations of Mandiangin Giant Gourami (Osphronemus goramy) - Nuryanto, Agus; Susilo, Maria Bramasti; Amurwanto, Adi (Jurnal Biodjati, 2019)
Â  Â Captive population of Mandiangin giant gourami (Osphronemus goramy Lac.) is a new strain developed from wild pop-ulations in Riam Kanan Dam. No much is known about the genetic constituent of this strain compared to the parental population. This re-search was done to obtain information whether genetic alteration has occurred in captive population compared to their wild parental pop-ulation. Wild population was caught from Riam Kanan Dam, while captive population was collected from Balai Perikanan Budidaya Air Tawar (BPBAT) â€œFreshwater Aquaculture Centreâ€ Mandiangin, South Kalimantan. The captive population of Batanghari strain from BPBAT Sungai Gelam, Jambi was also analyzed. Molecular assess-ment was done using CO1 PCR-RFLP which was developed by digest-ing the amplicon of the CO1 gene from all populations using two re-striction enzymes, namely HindIII and TaqI and resulted CO1-HindIII and CO1-TaqI RFLP markers. All tested populations showed uniform patterns of those CO1-RFLP markers but with different fragment sizes among populations. This means all resulted RFLP markers were mono-morphic in each populations but polymorphic among giant gourami populations. In other words, no genetic diversity within population but substantial genetic differences was observed between wild and cap-tive Mandiangin populations. This proved that genetic alteration has occurred in Mandiangin captive populations compared to the wild pa-rental giant gourami population. In conclusion, captive and wild pop-ulations of Mandiangin giant gourami were genetically different. This result is vital as scientific base for future development of inland fish-eries, especially for breeding strategy of Mandiangin giant gourami.Â 